GOOD CORPORATE GOVERNANCE DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN MELALUI CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - I Gusti Ayu Purnamawati; Gede Adi Yuniarta; Putu Ria Astria (Jurnal Keuangan dan Perbankan, 2017)
This research explained the relationship between Good Corporate Governance mechanism to company’s value, and the extent disclosure of Corporate Social Responsibility as moderation variable. Hierarchical regression analysis was used to examine modernization impact in the relationship between dependent and independent variable. Sample gathering was undertaken from 2012 to 2014. Tobin’s Q was used to assess the company’s value. Whereas Good Corporate Governance mechanism that was proxy by the number of managerial ownership and institutional ownership quantity was taken from ownership scale existed in company financial report. Extent measurement of Corporate Social Responsibility expressing was carried out by calculating each company’s CSR Index. This research used 44 samples of manufacturing companies meeting the criteria of purposive sampling. The testing of moderation effect and the main effect in the research was done using hierarchical regression analysis. The result showed that there was a positive and significant relationship between GCG mechanism and company value, whereas between CSR extent disclosure and company value there was an insignificant result. For examining the moderation impacts, CSR extent disclosure succeeded to moderate the relationship between managerial ownership and company value, but the extent of CSR expression did not succeed in moderating the relationship between institutional ownership and company value.